On Poisson law on groups - Ruchin, A. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Рухин. О законе Пуассона на группахA. Ruchinas. Apie Puasono dėsnį grupėse